1999
DOI: 10.1590/s1415-47571999000200021
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of resistance to soybean cyst nematode, Heterodera glycines ichione (Race 3), in a brazilian soybean population

Abstract: A study was made of the genetics of resistance to the soybean cyst nematode, race 3, in a population derived from crosses between the Brazilian soybean genotypes BR 90-4722 and FT-Cristalina. Crosses between the two parents were made, the F1 and F2 generations were obtained and the population was analyzed for the number of cysts found in each plant of each generation as well as the type of reaction to the nematode. The results showed that resistance to the cyst nematode in this soybean population is of a quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…HG Type 0 and HG Type 7 were found in 94 and 6% of tested populations, respectively. According to surveys of H. glycines races conducted in most soybean-growing areas in the world, race 3 is the most common race in the USA (Sikora & Noel, 1991;Niblack et al, 1993Niblack et al, , 2003Chen et al, 2001), in Japan (Riggs & Schmitt, 1991) and in Brazil (Mauro et al, 1999). The field populations of H. glycines in Iran seem to be less variable compared to other SCN populations in the world.…”
Section: Discussionmentioning
confidence: 99%
“…HG Type 0 and HG Type 7 were found in 94 and 6% of tested populations, respectively. According to surveys of H. glycines races conducted in most soybean-growing areas in the world, race 3 is the most common race in the USA (Sikora & Noel, 1991;Niblack et al, 1993Niblack et al, , 2003Chen et al, 2001), in Japan (Riggs & Schmitt, 1991) and in Brazil (Mauro et al, 1999). The field populations of H. glycines in Iran seem to be less variable compared to other SCN populations in the world.…”
Section: Discussionmentioning
confidence: 99%
“…Dominance effects were also ascertained to be important by several earlier researchers in the determination of resistance to NCS races 1 (Qiu et al, 1997;Yue et al, 2000), 2 (Yue et al, 2000), 3 (Matson & Williams, 1965;Rao-Arelli et al, 1992b;Rao-Arelli, 1994;Qiu et al, 1997;Di Mauro et al, 1999;Yue et al, 2000), 5 (Myers & Anand, 1991;Anand, 1994;Qiu et al, 1997;Yue et al, 2000) and 14 (Thomas et al, 1975;Yue et al, 2000) of SCN.…”
Section: Estimating Genetic Parameters Of Means and Variancesmentioning
confidence: 99%
“…This was most likely due to the presence of main-effect resistance genes. The presence of these genes justifies the use of qualitative methods in most studies on inheritance of resistance to H. glycines (Caldwell et al, 1960;Matson & Williams, 1965;Thomas et al, 1975;Hancock et al, 1987;Myers & Anand, 1991;Rao-Arelli et al, 1992a;Anand, 1994;Rao-Arelli, 1994;Young & Killen, 1994;Qiu et al, 1997;Di Mauro et al, 1999;Yue et al, 2000).…”
Section: Estimating the Number Of Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The control of the resistance to SCN in the cultivar Peking by three recessive genes, was reported by Caldwell et al (1960), while Matson and Williams (1965) identified only one dominant gene. Mauro et al (1999) identified one dominant gene and two recessive genes together controlling the resistance to race 3 in one line derived from the crossing of the cultivar FT-Cristalina (susceptible) and the line BR-904722, with resistance to race 3 acquired from the cultivar Peking.…”
Section: Inheritance Of Resistance Of Scnmentioning
confidence: 99%